Reflectin genes and development of iridophore patterns in Sepia officinalis embryos (Mollusca, Cephalopoda). Issue 5 (12th March 2013) - Andouche, Aude; Bassaglia, Yann; Baratte, Sébastien; Bonnaud, Laure
<x xml:space="preserve">Abstract</x> Background: In the cuttlefish Sepia officinalis, iridescence is known to play a role in patterning and communication. In iridophores, iridosomes are composed of reflectins, a protein family, which show great diversity in all cephalopod species. Iridosomes are established before hatching, but very little is known about how these cells are established, their distribution in embryos, or the contribution of each reflectin gene to iridosome structures. Results: Six reflectin genes are expressed during the development of iridosomes in Sepia officinalis. We show that they are expressed in numerous parts of the body before hatching. Evidence of the colocalization of two different genes of reflectin was found. Curiously, reflectin mRNA expression was no longer detectable at the time of hatchling, while reflectin proteins were present and gave rise to visible iridescence. Conclusion: These data suggest that several different forms of reflectins are simultaneously used to produce iridescence in S. officinalis and that mRNA production and translation are decoupled in time during iridosome development. Developmental Dynamics 242:550–561, 2013. © 2013 Wiley Periodicals, Inc.